2022
DOI: 10.3389/fneur.2022.879882
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio Is Associated With Circumferential Wall Enhancement of Unruptured Intracranial Aneurysm

Abstract: Background and PurposeNeutrophil-lymphocyte ratio (NLR) predicts clinical outcomes in patients with stroke. Aneurysm wall enhancement (AWE) on high-resolution vessel wall magnetic resonance imaging (HR-VWI) is an inflammation marker for intracranial aneurysm (IA). This study aims to evaluate the association of NLR as a peripheral blood inflammatory marker with circumferential AWE in patients with IA.MethodsWe analyzed data of consecutive patients harboring IAs between September 2017 and December 2021 at our in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…AWE on HR-VWI has been used as an imaging marker for vessel wall inflammation and aneurysm instability in patients with UIA. Recent studies showed the association of inflammatory blood biomarkers with AWE on HR-VWI in UIA patients (9)(10)(11)(12)(13). The plasma concentration of anti-inflammatory cytokine interleukin (IL)-10 in the aneurysm sac decreased in UIA with AWE (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…AWE on HR-VWI has been used as an imaging marker for vessel wall inflammation and aneurysm instability in patients with UIA. Recent studies showed the association of inflammatory blood biomarkers with AWE on HR-VWI in UIA patients (9)(10)(11)(12)(13). The plasma concentration of anti-inflammatory cytokine interleukin (IL)-10 in the aneurysm sac decreased in UIA with AWE (10).…”
Section: Discussionmentioning
confidence: 99%
“…The plasma concentration of anti-inflammatory cytokine interleukin (IL)-10 in the aneurysm sac decreased in UIA with AWE ( 10 ). Our previous study showed that the neutrophil-lymphocyte ratio as an inflammatory peripheral blood biomarker was associated with AWE on HR-VWI in UIA patients ( 12 ). The up-regulated proinflammatory IL-1β and down-regulated anti-inflammatory IL-1RA in the serum were associated with AWE on HR-VWI in 34 patients with UIA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammatory processes in the aneurysmal wall also involve the local activation of the immune system, including neutrophil influx followed by the infiltration of macrophages and other inflammatory cells (6,7). It has been reported that cytokine interleukin-10 and the neutrophil to lymphocyte ratio (NLR) are associated with AWE in HR-MRI (8,9). Given that AWE has emerged as an imaging biomarker of IA instability, a blood inflammatory index may reflect inflammatory processes in the aneurysmal wall and might thus serve as a new biomarker of IA instability.…”
Section: Introductionmentioning
confidence: 99%